STRATEGI SQ3R (SURVEY, QUESTION, READ, RECITE, DAN REVIEW) BERBASIS WACALIBEM SERI DALAM UPAYA MEMBANGUN KARAKTER GEMAR MEMBACA DI MTsN 3 JOMBANG - Swandari, Nurul; Jemani, Abdurahman (PAI FAI UNHASY Tebuireng Jombang, 2022)
Growing up the culture of reading fondness is carried out by families, educational units, and the community in collaboration with the government in an effort to increase interest in reading. This is stated in the Law of the Republic of Indonesia Number 43 of 2007. This research is a type of qualitative research using a case study strategy and research strategy which involves researchers to carefully investigate a program, event, activity, process, or what is being done by a group of individuals. The purpose of this research is to build the character and love of reading for the students of MTs Negeri 3 Jombang through the SQ3R Strategy (Survey, Question, Read, Recite, and Review) based on Wacalibem Seri. The results of the research achieved are: 1) Students are able to write resumes of reading results every day, 2) be able to create student books that will be collected by Indonesian language teachers at the end of the semester, and 3) Empower students' ability to tell biographies of characters after reading biographies. The SQ3R (Survey, Question, Read, Recite, and Review) strategy based on the Wacalibem Series is able to build a character who loves reading at MTs Negeri 3 Jombang.